Cerebral dopamine deficiency, plasma monoamine alterations and neurocognitive deficits in adults with phenylketonuria. Issue 16 (29th May 2017) - Boot, E.; Hollak, C. E. M.; Huijbregts, S. C. J.; Jahja, R.; van Vliet, D.; Nederveen, A. J.; Nieman, D. H.; Bosch, A. M.; Bour, L. J.; Bakermans, A. J.; Abeling, N. G. G. M.; Bassett, A. S.; et al.
Abstract : Background: Phenylketonuria (PKU), a genetic metabolic disorder that is characterized by the inability to convert phenylalanine to tyrosine, leads to severe intellectual disability and other cerebral complications if left untreated. Dietary treatment, initiated soon after birth, prevents most brain-related complications. A leading hypothesis postulates that a shortage of brain monoamines may be associated with neurocognitive deficits that are observable even in early-treated PKU. However, there is a paucity of evidence as yet for this hypothesis. Methods: We therefore assessed in vivo striatal dopamine D2/3 receptor (D2/3 R) availability and plasma monoamine metabolite levels together with measures of impulsivity and executive functioning in 18 adults with PKU and average intellect (31.2 ± 7.4 years, nine females), most of whom were early and continuously treated. Comparison data from 12 healthy controls that did not differ in gender and age were available. Results: Mean D2/3 R availability was significantly higher (13%; p = 0.032) in the PKU group ( n = 15) than in the controls, which may reflect reduced synaptic brain dopamine levels in PKU. The PKU group had lower plasma levels of homovanillic acid ( p < 0.001) and 3-methoxy-4-hydroxy-phenylglycol ( p < 0.0001), the predominant metabolites of dopamine and norepinephrine, respectively. Self-reported impulsivity levels were significantly higher in the PKU group compared with healthy controls ( p = 0.033). Within the PKU group, D2/3 R availability showed a positive correlation with both impulsivity ( r = 0.72, p = 0.003) and the error rate during a cognitive flexibility task ( r = 0.59, p = 0.020). Conclusions: These findings provide further support for the hypothesis that executive functioning deficits in treated adult PKU may be associated with cerebral dopamine deficiency.